Development of criteria and indicators for sustainable management of tropical plantation forests - Hopmans, P.; Prabhu, Ravi; Brand, D.; Nambiar, E.K.S.; Cossalter, C. (1998)
This paper examines the need to develop criteria and indicators (C&I) to assess the sustainability of tropical timber plantations. It does this in the light of expectations that such plantations are going to play an increasing role in meeting the demand for forest products, environmental services and social benefits. There is a need for sustainable management of these plantations in accordance with clearly defined objectives and values. It outlines a framework for sustainability in tropical forest plantations, the key issues involved in the development of appropriate C&I and concludes by sketching a role for CIFOR and its collaborators in developing such C&I.